Mind Your Step: A Sculptural Investigation of Spatial Awareness and Site - Walker, Charles (Auckland University of Technology, 2019)
Questioning my existence in this land and exploring the impact my presence has in it, Mind Your Step is a practice-led investigation searching multiple sites that combine to create a dialogue between process and material. Exploring a new environment and enquiring how materiality reflects my own observations. With a focus on Aotearoa, New Zealand and the landscape within Te Ika-a-Māui—the North Island, I look to establish a first-hand understanding of what has influenced the shaping of the landscape. Analysing how other artist’s practices explore ideas of site and history in an attempt to capture the essence of a place, through careful consideration for material and site with an ethic of care. I am questioning what it is to exist in a space, what it means to be a visitor in a space and how to conduct oneself. The materials glass, metal, and stone are used to sculpturally articulate my own experiences of geological movements and human activity. The overarching methodology of ‘the walk', a non-site observation, led this investigation. I am interested in paradigms around care, which I consider through my relationship with materials and how care influences decisions.
Keywords: Landscape; Site; Stone; Galss; Metal; Identity